Analysis of Madrasah Principal’s Leadership Style on Teachers’ Work Motivation - Chandra Chandra; Nur Ahyani; Nurlina Nurlina (PPSDP International Journal of Education, 2026)
This study aims to analyze the implementation of the principal’s leadership style, identify obstacles, and examine strategies for enhancing teacher work motivation at MI Luqmanul Hakim Marta Jaya. Employing a qualitative case study method, data were collected through interviews, observation, and documentation. The results indicate that the principal adopts an integrated leadership style, combining transformational, democratic, and Islamic values with minor transactional elements. Key obstacles include limited resources, administrative burdens, and varied teacher characteristics. Effective motivational strategies involve two-way communication, recognition, professional development, participatory decision-making, and cultivating an Islamic work environment. The novelty of this research lies in its focused examination of how Islamic values are synergized with contemporary leadership approaches in a madrasah setting. A key practical implication is that madrasah principals can adopt this integrated leadership model to foster motivation despite resource constraints. The study contributes a context-specific framework for faith-based educational leadership, demonstrating that purpose-driven and value-based practices are essential for sustaining teacher commitment in Islamic institutions.